2002
DOI: 10.1046/j.1469-8137.2002.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake by the floating macrophyte Lemna minor

Abstract: Summary• Both roots and leaves of free-floating plants can potentially take up nutrients. In this study, the ability and relative contribution of roots and fronds for N uptake by the floating macrophyte Lemna minor was investigated.• The NH 4 + and NO 3 -uptake kinetics of roots and fronds were measured on plants acclimated to three different NH 4 NO 3 concentrations.• Lemna had the capacity to take up NH 4 + and NO 3 -through both roots and fronds; uptake kinetics for the two tissue types were comparable on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 30 publications
9
86
2
2
Order By: Relevance
“…In addition, the high-nutrient sediment was favorable for the root growth of V. natans and the plant showed relatively high root length, as well as root area and root volume. Furthermore, SRL and SRA can be significantly affected by nutrient availability (Cedergreen & Madsen 2002;Xie & Yu 2003); high SRL and SRA are more favorable for nutrient acquisition in low-nutrient sediment (Eissenstat 1992). In the present study, SRL of V. natans was higher when SRA was higher at 120 cm in sandy loam, indicating that the plant has a relatively more efficient way to acquire nutrients from the low-nutrient sediment.…”
Section: Discussionsupporting
confidence: 44%
“…In addition, the high-nutrient sediment was favorable for the root growth of V. natans and the plant showed relatively high root length, as well as root area and root volume. Furthermore, SRL and SRA can be significantly affected by nutrient availability (Cedergreen & Madsen 2002;Xie & Yu 2003); high SRL and SRA are more favorable for nutrient acquisition in low-nutrient sediment (Eissenstat 1992). In the present study, SRL of V. natans was higher when SRA was higher at 120 cm in sandy loam, indicating that the plant has a relatively more efficient way to acquire nutrients from the low-nutrient sediment.…”
Section: Discussionsupporting
confidence: 44%
“…It was observed that the roots of both L. punatata OT and L. minor OT in mixture were considerably longer than those in monoculture in the low light intensity (unpublished data). In this regards, there is a long-standing controversy about root involvement in nutrient uptake in Lemnaceae species (Cedergreen and Madsen, 2002), but recent studies have shown that L. punctata can uptake nitrogen by both the roots and fronds (Fang et al 2007). Moreover, L. minor can regulate NO3 À uptake via fronds or roots depending on light intensity (Cedergreen and Madsen 2004).…”
Section: The Effect Of Light Intensity On Duckweed Growthmentioning
confidence: 99%
“…Thus, the N and P allocation to the submerged leaf does not inhibit the allocation of these nutrients to the floating leaves, and vice versa, at high or low concentrations in the structures. Cedergreen and Madsen (2002) saw that free-floating macrophytes obtain N and other nutrients directly from the water column through their roots and the underside of their leaves. In the case of S. auriculata, N is also translocated through the development of new ramets (Li and Wang, 2011).…”
Section: N and P Differential Allocation Between Floating Leaves And mentioning
confidence: 99%
“…Aquatic plants absorb nutrients through their leaves (Barko and Smart, 1986), while emergent macrophytes obtain N and P from the substratum, especially through their roots (Ran et al, 2004). Free-floating macrophytes obtain N and other nutrients directly from the water column through their roots and the underside of their leaves (Cedergreen and Madsen, 2002). In the case of S. auriculata, which produces clonal plants, N is not translocated only from the root to the shoot, but also through the development of new ramets (Li and Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%